2017
DOI: 10.1590/s1678-9946201759013
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of cryptococcosis and the characterization of Cryptococcus neoformans isolated in a Brazilian University Hospital

Abstract: Cryptococcosis, a systemic disease caused by the fungus Cryptococcus neoformans/ Cryptococcus gattii is more severe in immunocompromised individuals. This study aimed to analyze the epidemiology of the disease, the molecular characteristics and the antifungal susceptibility of C. neoformans isolated from patients treated in a Brazilian university hospital. This retrospective study was conducted in the Clinical Hospital, Federal University of Uberlândia, and evaluated cases of cryptococcosis and strains of C. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
(66 reference statements)
7
33
0
11
Order By: Relevance
“…Between the two, C. neoformans is the more common pathogen with a worldwide distribution and a tendency to infect immunocompromised hosts [1,2]. Historically, infection rates were highest amongst human immunodeficiency virus (HIV)-positive patients and C. neoformans was the leading cause of fungal-related death in these patients due to cryptococcal meningitis and sepsis [3,4]. However, improvements such as highly active antiretroviral therapy (HAART) have reduced HIV-related cryptococcal mortality in nations where the highest standard of care is widely available compared to developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…Between the two, C. neoformans is the more common pathogen with a worldwide distribution and a tendency to infect immunocompromised hosts [1,2]. Historically, infection rates were highest amongst human immunodeficiency virus (HIV)-positive patients and C. neoformans was the leading cause of fungal-related death in these patients due to cryptococcal meningitis and sepsis [3,4]. However, improvements such as highly active antiretroviral therapy (HAART) have reduced HIV-related cryptococcal mortality in nations where the highest standard of care is widely available compared to developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…70% of all infected patients in low-income countries to 20% of all infected patients in high-income countries (2). Although differences in mortality rates between high-and low-income countries can be linked to suboptimal antifungal treatments in low-income countries (3), variations in mortality rates between patient groups receiving similar treatments and residing in the same region of the world are observed (1,(4)(5)(6). Mortality is a measure influenced by many intrinsic host and pathogen factors (as well as host-pathogen interaction factors).…”
mentioning
confidence: 99%
“…Previous studies showed that pathogen-specific characteristics, such as the genotype or the degree of antigen shedding, influence immune responses to C. neoformans and the clinical outcome of patients (5,(7)(8)(9). Multilocus sequence typing (MLST) of 7 genetic loci has previously been used to identify genetically similar strains (5)(6)(7)(8)(9)(10). For example, studies of clinical isolates in both Uganda and Brazil showed higher patient mortality associated with sequence type 93 (ST93) strains (5,10).…”
mentioning
confidence: 99%
“…Mortality rates due to Cryptococcus infection varies by region from 70% in low-income countries to 20-40% of all infected patients in high-income countries (2). Although differences in mortality rates between high- and low-income countries can be linked to sub-optimal antifungal treatments in low-income countries (3), variations in mortality rates between patient groups receiving similar treatments and residing in the same region of the world are observed (1, 46). Mortality is a measure influenced by many intrinsic host and pathogen factors (as well as host-pathogen interaction factors).…”
Section: Introductionmentioning
confidence: 99%